2009
DOI: 10.1002/art.24706
|View full text |Cite
|
Sign up to set email alerts
|

Role of p53 in human chondrocyte apoptosis in response to shear strain

Abstract: Objective. Chondrocyte apoptosis plays an important role in cartilage degeneration in osteoarthritis (OA), and mechanical injury to cartilage induces chondrocyte apoptosis. In response to DNA damage, p53 expression is up-regulated, transcription activity is increased, and apoptosis signals are initiated. The p53-regulated apoptosis-inducing protein 1 (p53AIP-1) is one of the p53-regulated genes, and is activated in response to DNA damage. This study was undertaken to analyze p53 function after induction of apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 35 publications
2
55
0
1
Order By: Relevance
“…It is known that p53 induces cell death in articular as well as Meckel's cartilage (Trichilis and Wroblewski, 1997;Okazaki et al, 2003). In human chondrocyte culture, PFT treatment suppresses p-p53-Ser15 as well as chondrocyte apoptosis induced by mechanical stress (Hashimoto et al, 2009). Additional studies with PFT are necessary to identify the cell type that is responsible for the nasal phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that p53 induces cell death in articular as well as Meckel's cartilage (Trichilis and Wroblewski, 1997;Okazaki et al, 2003). In human chondrocyte culture, PFT treatment suppresses p-p53-Ser15 as well as chondrocyte apoptosis induced by mechanical stress (Hashimoto et al, 2009). Additional studies with PFT are necessary to identify the cell type that is responsible for the nasal phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, optimal mechanical stress stimulation was shown to maintain the structure and function of articular cartilage, whereas excessive mechanical force was shown to lead to a loss of cartilage and the onset of OA (31-33). In addition, we have previously demonstrated that excessive shear stress induces chodrocyte apoptosis via the p53 pathway (34).…”
Section: Discussionmentioning
confidence: 97%
“…Threshold stresses and strains for cartilage matrix damage and cell death are shown to be dependent on rate of loading [56,59,86,87], duration of load [85,89], and magnitude of load [56,59,85,88,89]. However, maximum shear strain has been identified as one major failure mode for the cartilage matrix [57,58].…”
Section: Cartilage Matrix Damage and Chondrocyte Apoptosismentioning
confidence: 99%
“…show that there is a strong positive association between cartilage matrix damage and chondrocyte apoptosis [84], indicating that prolonged or large magnitude impact loading causing tissue damage also leads to cell death [56,59,85,86,87,88,89].…”
Section: Cartilage Matrix Damage and Chondrocyte Apoptosismentioning
confidence: 99%
See 1 more Smart Citation